Ursus arctos subsp. arctos Linnaeus 1758 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ursus arctos subsp. arctos Linnaeus 1758 Ursus arctos subsp. arctos Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 47. Type Locality: "sylvis Europæ frigidæ" restricted by Thomas (1911 a ) to "Northern Sweden.". Synonyms: Ursus arctos subsp. albus Gmelin 1788; Ursus arctos subsp. alpinus G. Fischer 1814; Ursus arctos subsp. annulatus Billberg 1827; Ursus arctos subsp. argenteus Billberg 1827; Ursus arctos subsp. aureus Fitzinger 1855; Ursus arctos subsp. badius Schrank 1798; Ursus arctos subsp. brunneus Billberg 1827; Ursus arctos subsp. cadaverinus Eversmann 1840; Ursus arctos subsp. euryrhinus Nilsson 1847; Ursus arctos subsp. eversmanni (Gray 1864); Ursus arctos subsp. falciger Reichenbach 1836; Ursus arctos subsp. formicarius Billberg 1828; Ursus arctos subsp. fuscus Gmelin 1788; Ursus arctos subsp. grandis J. E. Gray 1864; Ursus arctos subsp. griseus Kerr 1792; Ursus arctos subsp. gobiensis Sokolov and Orlov 1992; Ursus arctos subsp. longirostris Eversmann 1840; Ursus arctos subsp. major Nilsson 1820; Ursus arctos subsp. marsicanus Altobello 1921; Ursus arctos subsp. minor Nilsson 1820; Ursus arctos subsp. myrmephagus Billberg 1827; Ursus arctos subsp. niger Gmelin 1788; Ursus arctos subsp. normalis Gray 1864; Ursus arctos subsp. norvegicus J. B. Fischer 1829; Ursus arctos subsp. polonicus J. E. Gray 1864; Ursus arctos subsp. pyrenaicus J. B. Fischer 1829; Ursus arctos subsp. rossicus J. E. Gray 1864; Ursus arctos subsp. rufus Borkhausen 1797; Ursus arctos subsp. scandinavicus Gray 1864; Ursus arctos subsp. stenorostris Gray 1864. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 588, DOI: 10.5281/zenodo.7316519